A 10-year follow-up of therapeutic rehabilitation in a child with LMNA-associated congenital muscular dystrophy: a case report - Liu, Zhimei; Zhao, Shuo; Wang, Ziheng; Chen, Minhua; Cai, Kelong; Yang, Kang (Journal of the Pakistan Medical Association, 2026)
Lamin A/C (LMNA)-associated congenital muscular dystrophy (L-CMD) is a rare neuromuscular disorder caused by mutations in the LMNA gene, characterised by droopy head syndrome with motor developmental delays and weakness of the spinal axial and proximal muscles of the extremities. This case report describes the 10-year therapeutic rehabilitation and follow-up of an 18-month-old girl whose parents complained of slender neck and muscle weakness at the Rehabilitation Medicine Department, Northern Jiangsu People’s Hospital, Yangzhou, China. The purpose of this case report is to demonstrate that early, continuous, and systematic motor rehabilitation training proved to be conducive to the development of motor function in this L-CMD child. Keywords: LMNA-related congenital muscular dystrophy, Genetic deficiency, Therapeutic rehabilitation, Motor function.